Illusions of inclusion: typical mistakes of parents of ASD children. Inclusive school experience - Khotyleva T.U; Rosenblum S.A (Moscow State University of Psychology and Education, 2017)
Despite the great motivation for sending children with autism disorders into inclusive educational organiza¬tions, unpreparedness of some parents for real inclusion can interrupt constructive interaction with the school. Meanwhile, effective interaction between the school and parents is one of the main factors of successful inclusive education. Such interaction is provided by the psychological and pedagogical services of the school. Long stand¬ing experience of specialists of inclusive high school № 1540 allowed authors to analyze the erroneous views on inclusive education of parents with ASD children. Typical mistakes of parents are described and the need for informed child's future planning which includes the development of emotional intelligence is emphasized.